In vivo evaluation of riboflavin receptor targeted fluorescent USPIO in mice with prostate cancer xenografts - Jayapaul, Jabadurai; Arns, Susanne; Bunker, Matt; Weiler, Marek; Rutherford, Sandra; Comba, Peter; Kiessling, Fabian (Nano research, 2016)
Riboflavin (Rf) receptors bind and translocate Rf and its phosphorylated forms (e.g. flavin mononucleotide, FMN) into cells where they mediate various cellular metabolic pathways. Previously, we showed that FMN-coated ultrasmall superparamagnetic iron oxide (FLUSPIO) nanoparticles are suitable for labeling metabolically active cancer and endothelial cells in vitro. In this study, we focused on the in vivo application of FLUSPIO using prostate cancer xenografts. Size, charge, and chemical composition of FLUSPIO were evaluated. We explored the in vitro specificity of FLUSPIO for its cellular receptors using magnetic resonance imaging (MRI) and Prussian blue staining. Competitive binding experiments were performed in vivo by injecting free FMN in excess. Bio-distribution of FLUSPIO was determined by estimating iron content in organs and tumors using a colorimetric assay. AFM analysis and zeta potential measurements revealed a particulate morphology approximately 20-40 nm in size and a negative zeta potential (-24.23 ± 0.15 mV) in water. X-ray photoelectron spectroscopy and time-of-flight secondary ion mass spectrometry data confirmed FMN present on the USPIO nanoparticle surface. FLUSPIO uptake in prostate cancer cells and human umbilical vein endothelial cells was significantly higher than that of control USPIO, while addition of excess of free FMN reduced accumulation. Similarly, in vivo MRI and histology showed specific FLUSPIO uptake by prostate cancer cells, tumor endothelial cells, and tumor-associated macrophages. Besides prominent tumor accumulation, FLUSPIO accumulated in the liver, spleen, lung, and skin. Hence, our data strengthen our hypothesis that targeting riboflavin receptors is an efficient approach to accumulate nanomedicines in tumors opening perspectives for the development of diagnostic and therapeutic systems.
Gesehen am 30.04.2020